The use of huff and puff method in a single horizontal well in gas production from marine gas hydrate deposits in the Shenhu Area of South China Sea - Li, Gang; Moridis, George J.; Zhang, Keni; Li, Xiao-sen (Journal of Petroleum Science and Engineering, 2011)
The Shenhu Area is located in the Pearl River Mouth Basin, the northern continental slope of the South China Sea. It is expected that the Shenhu Area will become a strategic area of gas hydrate exploitation in China. Based on currently available data from site measurements, including water depth, thickness of the Hydrate-Bearing Layer (HBL), sediment porosity, salinity and pressures and temperatures at key locations, it is possible to develop preliminarily estimates of the gas production potential by numerical modeling.